Impact of the pandemic on social protection centers for the elderly and the government response in Cali - Colombia. - Torres-Agredo, Miyerlandi (2022)
Introduction: The impact of COVID-19 worldwide has caused enormous changes and challenges. Several risk groups have been identified, which more easily develop severe and critical forms of the disease. On the one hand, older adults, mainly over 80 years of age, and on the other hand, people with chronic diseases such as cardiovascular disease, diabetes mellitus, chronic respiratory disease, and cancer. Aim: To present the actions carried out by the Secretaría de Salud Pública (SSP) for the mitigation and containment of COVID-19 in the residents of the Centros de Protección Social del Adulto Mayor (CPSAM) in the district of Santiago de Cali. Materials and methods: Since the month of February 2020, since before the arrival of the virus in the country; The SSP initiated actions aimed at maintaining a low number of COVID-19 outbreaks and therefore low mortality. The actions were carried out according to the network system design in which the different organizations in charge of insurance and patient care in the city were involved, all under a single coordination. The SSP work teams were strengthened and actions were implemented such as the characterization of the centers and institutionalized older adults, guidelines and technical assistance for those involved in care, virtual and face-to-face advice to accompany disinfection procedures and waste management and the sectorial coordination, in which the SSP coordinated the actions in the CPSAM and the entities in charge of providing health services. Results: During the first months of the pandemic, the existence of 194 centers was identified that to date provided care to 3,510 elderly people and had almost 1,500 workers in charge of operation. 2,494 older adults were quickly characterized, of which 1,906 institutionalized in 92 CPSAM were approached by the district's health service providers. As with morbidity from COVID-19, deaths had oscillating periods in which the months of July and August 2020 and January 2021 stand out with a lower case fatality rate compared to other countries. Conclusions: The articulated response allowed the CPSAM to intervene comprehensively with preventive and intervention actions when necessary.